Night Shift Work Accelerates Menopausal Age in Health Workers - Sri Ratna Dwiningsih; Samsulhadi Samsulhadi; Arif Tunjungseto; Monika Lijuwardi; Arsana Wiyasa (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2021)
Introduction: Earlier menopause has been associated with increased risk of cardiovascular disease, osteoporosis, shorter life expectancy and even cognitive decline. There are many factors that cause differences in the age of menopause in women, one of these environmental factors is a history of night shift work as a consequence of a job. It is not yet known whether female medical workers, with a history of night shifts, get earlier menopause.Methods: This case control study was conducted among 57 female night workers of the Dr. Soetomo General Academic Hospital. Data collection was conducted from December 2019 - March 2020. The study sample was postmenopausal health workers (nurse and midwife) and administrators. The instrument used in this study was a list of interview questions. The data was processed using SPSS software release 23.Results: The results show that from 45 children diagnosed with ALL, 53% are of the age ≤ 5 years old, with 58% males and 42% females. 13% of the patients are in the high risk group and 87% are in the standard risk group. Nutritional statuses of patients are 2% of them obese experienced remission after induction phase therapy, 56% normal with 80% of them experienced remission. 40% underweight with 89% of them experienced remission and 11% not experienced remission, 2% malnutrition and experienced remission. There is no correlation between the nutritional status of children with acute lymphoblastic leukemia with the outcome of induction phase (p = 0.798).Conclusion: In conclusion, there is no correlation between nutritional status and remission outcome of patients with ALL in the induction phase of therapy. However, high percentage of underweight patients shows nutrition needs special attention to improve therapy outcomes.